Determinan Manajemen Laba pada Perusahaan Sektor Basic Materials yang Terdaftar di Bursa Efek Indonesia Peri-ode 2022–2024 - Devin Raynadi Wiguna; Geraldo Jose Reynaldi; Kusuma Dewi; Ervina Indri Sari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to evaluate the impact of firm size, gender diversity on the board of directors, and firm growth on earnings management practices in Basic Materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, using the agency theory framework. This quantitative research uses secondary data from the company's annual reports. The population includes all companies in the Basic Materials sector, while the sample was determined via purposive sampling. Data were analyzed using multiple linear regression on panel data, and estimation was performed using the fixed effects model in EViews 12. After classical assumption testing and model selection, the research results indicate that firm size and firm growth strengthen earnings management practices, while gender diversity has no significant effect. These findings support the implications of agency theory that incentives and increased monitoring needs, which grow with company size and growth, drive earnings management practices, while also providing empirical contributions to strengthening corporate governance and monitoring mechanisms.